Analysis of product disassemblability using the disassembly evaluation chart methodology - Wiwiek Fatmawati, Wiwiek Fatmawati (2007)
Designing product which is safe for the environment and facilitate the product and its parts to be easily reused, remanufactured or recycled at its end of life is becoming increasingly important. One of the aspects of product development which focus on the recovery of resources at the end of the product lifecycle is Design for Disassembly (DFD). Disassembly evaluation chart methodology (DECM) is one of the various available methods in DFD which can be used to evaluate the disassemblability of a product by using a spreadsheet-like chart with the respect to the disassembly difficultness for each task of the disassembly operation which is derived from the Maynard Operation Sequence Technique (MOST) system. The goal of DECM is to make products easier to disassemble. The evaluation result such as disassembly efficiency, disassembly time and disassembly cost estimation are calculated and then evaluated to identify what should be improved. The design optimization is achieved by reviewing the evaluation results, making improvements on the design and re-evaluates the design. Validation of DECM is done by using a product case study and comparing the result from the original design to the proposed design of product case study. Results obtained from the case study showed that the method is able to achieve objectives of the product disassembability.